The The Effect of GRDP and Minimum Wage on Open Unemployment Rate in East Java Province - Indrawati, Anik; Eviana Hutabarat, Ruth (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to determine the effect of gross regional domestic product and minimum wage on the open unemployment rate in East Java province. The data used in this study is panel data of 38 districts / cities from 2018-2022. The data source comes from the official website of Badan Pusat Statistik. The research method used in this research is quantitative method. The results showed that partially the Gross Regional Domestic Product (GRDP) has a significant and negative effect on the open unemployment rate. Meanwhile, the minimum wage has a significant and positive effect on the level of open unemployment. Simultaneously, Gross Regional Domestic Product (GRDP) and minimum wage have a significant influence on the open unemployment rate.